PENGARUH PENAMBAHAN KONSENTRASI JAMUR KUPING TERHADAP UJI ORGANOLEPTIK BAKSO DAGING SAPI - Nadila Nur Azizah; Agustina Widyasworo (AVES: Jurnal Ilmu Peternakan, 2019)
This research was carried out in Balitar Islamic University Laboratory. It is located at Jl. Majapahit no 4 Blitar. This research was conducted in July 2019. The purpose of this study was to determine the effect of substitution of ear mushroom concentration on organoleptic tests of meatballs. This research is expected to be an input for meatball traders to overcome the price of meat that is too high. This study used ear mushroom of 0%, 35%, 40%, and 45%. The method used in this research is experiment. The results of this study are very significant differences in the color and flavor of meatballs with ear mushroom substitution. There is significant difference in texture but there is not significant difference in the taste of beef meatballs with ear mushroom substitution. Because ear mushroom have taste as beef and are rich in vegetable protein.